CGIAR System Internal Audit Function CHARTER - CGIAR System Organization (CGIAR System Organization, 2018)
This document further establishes in practical terms Internal Audit Function’s purpose, authority, responsibility and position within the organization. The terms described in this document apply regardless of the composition, nature and the source of the entity that provides the internal audit services to the governing bodies of the CGIAR System.